Ethical issues in the halal food supply chain: A systematic bibliometric review - Mohamad Reeduan, Mustapha; Farhana, Ahamad; Noor Yuslida, Hazahari; Nurhusna, Samsudin (Emerald Publishing Limited, 2024)
Purpose; Systematic reviews have contributed substantially to the development of knowledge in various academic fields and have helped discover new research potentials in a systematic manner. Specifically, this study aims to conduct a systematic bibliometric review to address ethical issues across the halal food supply chain (HFSC), as well as to identify the ethical challenges that food handlers face in ensuring authenticity, compliance with Shariah law and avoidance of contamination with non-halal ingredients in halal food products. Design/methodology/approach; A bibliometric approach was used to analyse 263 publications from the Scopus database. The present research analysed the documents’ bibliographical data based on publication year, source title, country of origin, institution, authorship, keywords and citation count. The VOSviewer software was applied to perform citation and co-word analysis, as well as to construct bibliometric networks centred on the topic of ethical issues in the HFSC. This bibliometric review provides valuable insights for researchers to identify key publications and comprehend the foundational structure of the subject matter. It also helps guide future research into significant trends and new areas of study. Findings; Citation analysis provides valuable insights into influential publications and the interconnectedness of research on HFSC. A co-word analysis revealed that discussions on ethics and integrity in the HFSC primarily revolved around the concept of halal and its implications, particularly in supply chain management. However, the limited frequency and prominence of these keywords suggests a scarcity of academic discourse on ethical matters in this field. Moreover, ethical considerations not only serve as a critical aspect of ensuring halal integrity but also emerge as a strategic imperative in marketing, brand management and the operation of global businesses. Originality/value; This study addresses the need to examine the knowledge gap in the literature on ethical practices and issues in HFSC. Although there is a significant amount of academic writing in the halal context, there is a scarcity of research that specifically focuses on the ethical aspects of HFSC. This study also offers a framework for investigating the ethical practices and issues in HFSC.